2014
DOI: 10.1002/anie.201408476
|View full text |Cite
|
Sign up to set email alerts
|

Specific Light‐Up Bioprobe with Aggregation‐Induced Emission and Activatable Photoactivity for the Targeted and Image‐Guided Photodynamic Ablation of Cancer Cells

Abstract: Activatable photosensitizers (PSs) have been widely used for the simultaneous fluorescence imaging and photodynamic ablation of cancer cells. However, the ready aggregation of traditional PSs in aqueous media can lead to fluorescence quenching as well as reduced phototoxicity even in the activated form. We have developed a series of PSs that show aggregation-enhanced emission and phototoxicity and thus the exact opposite behavior to that of previously reported PSs. We further developed a dual-targeted enzyme-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
269
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 484 publications
(272 citation statements)
references
References 42 publications
2
269
0
1
Order By: Relevance
“…[82] Recently, Liu et al described a series of special fluorophores that possess aggregation-induced emission (AIE) characteristics that can be used advantageously in the design of new aPSs. [83][84][85] One system is a dual-selective enzyme-responsive bioprobe containing a PS for cancer-specific imaging and activatable PDT. [83] The probe is composed of four parts including an AIE fluorogen for imaging and PS, a GFLG peptide with cathepsin B responsive properties, a specific tri-Asp linker for improved hydrophilicity, and a cRGD-targeting group.…”
Section: Figure 12mentioning
confidence: 99%
See 2 more Smart Citations
“…[82] Recently, Liu et al described a series of special fluorophores that possess aggregation-induced emission (AIE) characteristics that can be used advantageously in the design of new aPSs. [83][84][85] One system is a dual-selective enzyme-responsive bioprobe containing a PS for cancer-specific imaging and activatable PDT. [83] The probe is composed of four parts including an AIE fluorogen for imaging and PS, a GFLG peptide with cathepsin B responsive properties, a specific tri-Asp linker for improved hydrophilicity, and a cRGD-targeting group.…”
Section: Figure 12mentioning
confidence: 99%
“…[83][84][85] One system is a dual-selective enzyme-responsive bioprobe containing a PS for cancer-specific imaging and activatable PDT. [83] The probe is composed of four parts including an AIE fluorogen for imaging and PS, a GFLG peptide with cathepsin B responsive properties, a specific tri-Asp linker for improved hydrophilicity, and a cRGD-targeting group. In aqueous media, the photoactivities of the probe are quenched by the absence of exciton energy induced by intramolecular motions.…”
Section: Figure 12mentioning
confidence: 99%
See 1 more Smart Citation
“…These AIEgens such as tetraphenylethene (TPE) are propeller shaped, which emit almost no fl uorescence when molecularly dissolved but could be induced to become highly emissive in aggregate state due to the prohibition of energy dissipation and restriction of intramolecular rotation (RIR). [ 62,[67][68][69][70] The unique feature of AIEgens has made them valuable in the development of lightup probes, [ 13,[71][72][73] and ultrabright organic dots [74][75][76][77][78][79] for sensing and imaging applications. Very recently, we and others also found that several AIEgens show effi cient ROS production in aggregate state.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, we and others also found that several AIEgens show effi cient ROS production in aggregate state. [ 72,[80][81][82] These unique properties are ideal for mitochondria-targeted PDT as the accumulation of AIEgens in mitochondria or encapsulation of AIEgens by mitochondria-targeted nanocarriers will not compromise their fl uorescence and ROS generation.…”
Section: Introductionmentioning
confidence: 99%